2017
DOI: 10.1126/scitranslmed.aam9078
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of PGBD5-induced DNA repair dependency in pediatric solid tumors

Abstract: Despite intense efforts, the cure rates of childhood and adult solid tumors are not satisfactory. Resistance to intensive chemotherapy is common, and targets for molecular therapies are largely undefined. We have now found that the majority of childhood solid tumors, including rhabdoid tumors, neuroblastoma, medulloblastoma and Ewing sarcoma, express an active DNA transposase PGBD5 that can promote site-specific genomic rearrangements in human cells. Using functional genetic approaches, we found that mouse and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 69 publications
5
37
0
Order By: Relevance
“…Importantly, supervised analysis of distinct tumor specimens revealed potentially new tumor markers, such as PGBD5 (Supplemental Figure 1B), which we recently validated as an oncogenic DNA transposase and therapeutic target in rhabdoid tumors (14)(15)(16)(17). In the case of favorable-histology Wilms' tumor, we identified the most abundant proteins specifically detected in Wilms' tumor as compared with other non-Wilms' tumor kidney tumor urine specimens (Supplemental Figures 1, B-E).…”
Section: Comparative Urine Proteomics Of Wilms' Tumor Kidney Rhabdoimentioning
confidence: 77%
See 1 more Smart Citation
“…Importantly, supervised analysis of distinct tumor specimens revealed potentially new tumor markers, such as PGBD5 (Supplemental Figure 1B), which we recently validated as an oncogenic DNA transposase and therapeutic target in rhabdoid tumors (14)(15)(16)(17). In the case of favorable-histology Wilms' tumor, we identified the most abundant proteins specifically detected in Wilms' tumor as compared with other non-Wilms' tumor kidney tumor urine specimens (Supplemental Figures 1, B-E).…”
Section: Comparative Urine Proteomics Of Wilms' Tumor Kidney Rhabdoimentioning
confidence: 77%
“…First, reported urine proteome profiles of diverse kidney tumors provide a valuable source of potential tumor biomarkers and therapeutic targets. Our recent study of PGBD5, identified in the proteomic profiles of renal rhabdoid tumors, revealed an unanticipated mechanism of human tumor pathogenesis and molecular target for improved therapy (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Unless an effective repair mechanism corrects the damage to the double helix, DNA damage may cause persistent abnormalities after mitosis and in irreplaceable cells such as neurons (Milanese et al, 2018). Fortunately, cells have evolved DNA damage repair (DDR) mechanisms to alleviate a variety of damages (Henssen et al, 2017). Once DNA damage is triggered by exogenous and endogenous factors such as free radicals, the DDR can be activated to alter expressions of the damage sensor γ-H2AX and subsequent signal transduction pathways such as ATM/Chk2 pathway-related proteins (Ronco et al, 2017;He et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…DDR DNA damage response, PARP poly(ADP-ribose) polymerase, PARG poly(ADP-ribose) glycohydrolase have identified the mechanism of ATR inhibitor resistance in vitro. Henssen et al [159] recently reported that endogenous PGBD5 depletion is associated with AZD6738 resistance in human tumor cells. AZD6738 causes unrepaired DNA damage to be accumulated in PGBD5-expressing cells, resulting in G1-phase and dividing cell apoptosis.…”
Section: Resistance To Atr Inhibitorsmentioning
confidence: 99%